(untitled) (Impetus, 2026)
The present study examines the implementation of Project Based Learning (PBL) in the subject Physical Activity, Health and Society, within the Spanish curriculum of the second year of Bachillerato. The research was carried out in a public school located in a rural setting in southern Andalusia (Spain) and involved 38 students enrolled in the subject (15 boys and 23 girls). A qualitative analysis was used. The results reflect a mostly positive perception on the part of the students, highlighting the diversity of activities, collaborative work and participatory methodology as key factors in the learning process. Likewise, PBL showed a significant impact on the development of social and civic competencies, favoring active involvement and autonomy. However, it is necessary to improve: time management, availability of resources and students’ attitude. Despite these challenges, teacher intervention played an essential role in creating a positive learning environment, contributing to student motivation and engagement. In conclusion, the findings support the suitability of PBL in Physical Education in the baccalaureate, although it is necessary to optimize its planning to maximize its effectiveness and sustainability in future implementations.